Juvenile Delinquency and Its Coping Strategy: An Islamic Education Perspective - Hamidi, Nur; Nurdin, Indra Fajar (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
This research is aimed to portrait the juvenile delinquency and strategy to cope it from Islamic education point of view. The fact that numbers of juvenile delinquency is increasing from time to time has become ironic because the adolescents involved in delinquency and crime are also students. School is a place that formally not only to provide students with knowledge and science, but also to educate them to have good character and attitude. This type of research, seen from the data collection point of view, is a type of library research by using content analysis method in analysing data. The research found that from the islamic education perspective, the synchronization of education between the family environment, community environment and school environment in the form of cultivation of morality/religion in the family, cultivation of morals/religion in schools and also by widening knowledge is the best strategy in coping juvenile delinquency.